Analisis Faktor-Faktor yang Mempengaruhi Implementasi Akuntansi Akrual pada Entitas Pemerintah Daerah - Usman, Usman; Sunandar, Sunandar; Farida, Ida (Journal of Accounting and Investment, 2014)
This research aims to provide an overview and empirical evidence regarding the level of implementation of accrual accounting in the local government, especially at the level of the working unit. Collecting data in this study using a questionnaire survey. The population of the research object in this case is the Budget Authority Users of the Local Government Unit (SKPD) Department of Industry, Trade, Koperasi and SMEs Ponorogo 2014. The data collected were processed using multiple linear regression analysis. The results of this research show that the level of implementation of accrual accounting in the Government is still very low. In particular the level of implementation of accrual accounting is influenced significantly by the financial staff training. However, there were no significant effects of the educational level of staff, quality of information technology consulting, support, experience, educational background and a work unit size against the level of implementation of accrual accounting.